2011
DOI: 10.1159/000332980
|View full text |Cite
|
Sign up to set email alerts
|

Indications for the Use of Probiotics in Gastrointestinal Diseases

Abstract: Probiotics are live microbial organisms that are present in foods or dietary supplements and that confer health benefits to the host when ingested in sufficient quantities. Probiotics can be bacterial (e.g. Bifidobacteria spp. and Lactobacillus spp.) or yeasts (e.g. Saccharomyces boulardii). The administration of probiotics is often believed to be by and large beneficial for individuals with inflammatory or infectious diseases of the gastrointestinal tract. These positive effects are generally attributed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 218 publications
0
34
0
13
Order By: Relevance
“…BO biofilm has generated the possibility of involving microbes in BO progression and therefore probiotics might influence and restrain molecular modifications of BO movements. Studies have shown that beneficial micro-organisms have positive effects in controlling gastrointestinal diseases (Macfarlane et al, 2008;Girardin & Seidman, 2011;Weng & Walker, 2013). Subsequently, this study investigated the possible role of B. longum and L. acidophilus in the inhibition of those biomarkers that contribute to BO transformation such as IL-18, TNFa, p53, COX2 and CDX1.…”
Section: Discussionmentioning
confidence: 99%
“…BO biofilm has generated the possibility of involving microbes in BO progression and therefore probiotics might influence and restrain molecular modifications of BO movements. Studies have shown that beneficial micro-organisms have positive effects in controlling gastrointestinal diseases (Macfarlane et al, 2008;Girardin & Seidman, 2011;Weng & Walker, 2013). Subsequently, this study investigated the possible role of B. longum and L. acidophilus in the inhibition of those biomarkers that contribute to BO transformation such as IL-18, TNFa, p53, COX2 and CDX1.…”
Section: Discussionmentioning
confidence: 99%
“…Each probiotic has a different mechanism of action and as such, not all probiotics will have the same effect after ingestion. Some beneficial effects are common to several probiotic species, while others are specific to particular species [6].…”
Section: Mechanism Of Probiotic Action In Ibdmentioning
confidence: 99%
“…Positive effects of probiotics are generally attributed to their ability to normalize host intestinal flora, modulate the intestinal epithelial barrier of the host, block pathogen binding to or penetration of mucosal surfaces, prevent the pathogenic bacterial growth, stimulate mucosal barrier function, and equilibrate the balance between proinflammatory and anti-inflammatory cytokines and subsequently reduce the severity of the intestinal inflammation associated with IBD [6,7]. This review will explore various mechanisms by which probiotics may affect IBD and summarize the current knowledge regarding the role of probiotics in IBD.…”
Section: Introductionmentioning
confidence: 99%
“…· Los probióticos. Constituidos por microorganismos vivientes potencialmente benéfi cos para nuestro organismo, los probióticos han mostrado gran utilidad en prevenir infecciones gastrointestinales 45 . En relación a prevenir ITUs, su utilidad ha sido especialmente documentada en mujeres y con ciertas cepas de Lactobacillus 46 .…”
Section: Controversia 5 Del Uso De Otras Medidas Preventivasunclassified